2023
DOI: 10.3390/membranes13030280
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of Microfiltration Process for Purifying Lactic Acid in the Fermented Broth of Kitchen Waste

Abstract: Fermentation broth is plentiful with lactic acid, an important chemical applied in many fields, such as food processing, the chemical industry, and cosmetics. However, the purification of the lactic acid from the broth is still troublesome, when considering the economy. This study first investigated the purification performance of microfiltration (MF) membrane technology for a fermentation broth from kitchen waste. The effect of operation pressure, broth pH, and membrane flushing mode on the membrane filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Additionally, the highest possible value added of the separated products is obtained to enhance the economy. This current Special Issue titled “Separation Techniques and Circular Economy” in Membranes presents the novel separation technologies involving the recovery of extracellular polymeric substances (EPSs) [ 1 ], calcium alginate (Ca-Alg) [ 2 ] in wastewater treatment, plasmid DNA in gene therapy [ 3 ], lactose in dairy industry [ 4 ], lactic acid (LA) in the fermented broth of kitchen waste [ 5 , 6 ], phenylalanine losses in neutralization dialysis (ND) [ 7 ], the removal of secondary effluent organic matter (EfOM) [ 8 ], and acetaldehyde (CH 3 CHO) in the atmosphere [ 9 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the highest possible value added of the separated products is obtained to enhance the economy. This current Special Issue titled “Separation Techniques and Circular Economy” in Membranes presents the novel separation technologies involving the recovery of extracellular polymeric substances (EPSs) [ 1 ], calcium alginate (Ca-Alg) [ 2 ] in wastewater treatment, plasmid DNA in gene therapy [ 3 ], lactose in dairy industry [ 4 ], lactic acid (LA) in the fermented broth of kitchen waste [ 5 , 6 ], phenylalanine losses in neutralization dialysis (ND) [ 7 ], the removal of secondary effluent organic matter (EfOM) [ 8 ], and acetaldehyde (CH 3 CHO) in the atmosphere [ 9 ].…”
mentioning
confidence: 99%
“…However, the purification of the LA from the broth is still troublesome when considering the economy. The purification performance of MF membrane technology for a fermentation broth from kitchen waste was investigated [ 5 ]. The results indicated that the MF process could be a desirable broth purification process to some extent, and it is promising in actual application.…”
mentioning
confidence: 99%